Evaluation of intrapulmonary arteriovenous anastomoses before and after oxygen supplementation, using transthoracic agitated saline contrast echocardiography in rescued Korean raccoon dogs - Lee, Chang-eun; Kim, Myeongsu; Han, Jae-Ik; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2024)
Introduction: Intrapulmonary arteriovenous anastomoses (IPAVAs) are defined as relatively large, dynamic shunt vessels that connect the pulmonary arterial and venous systems, thereby bypassing the pulmonary capillary system. IPAVAs lower elevated pulmonary arterial pressure; however, the presence of the shunt can result in impaired pulmonary gas exchange and paradoxical embolism. Furthermore, the prevalence and effects of IPAVAs in raccoon dogs remain unknown. This study aimed to determine the prevalence of IPAVA among rescued Korean raccoon dogs and evaluate the changes in IPAVA following oxygen supplementation. Methods: Nineteen raccoon dogs rescued by the Jeonbuk Wildlife Center between August 2022 and December 2023 were subjected to echocardiography. Sixteen healthy and three abnormal raccoon dogs were subjected to transthoracic agitated saline contrast echocardiography (bubble study) based on the echocardiography results. IPAVA was considered to be present if the left heart contrast was visualised after four cardiac cycles following the visualisation of the first right heart contrast. Bubble scores (BS0–5) were assigned based on the maximum number of microbubbles observed in the left ventricular lumen per frame of the ultrasound image. BS was assigned before and after supplementation with 100% oxygen for 5 min. Results: IPAVA was detected in 12 of the 16 healthy raccoon dogs at rest (75%). The BS of the 15 IPAVA-positive raccoon dogs ranged from 1–4 points (BS1, 1; BS2, 4; BS3, 8; and BS4, 2 ). Blood flow through the IPAVA (QIPAVA) was reduced or absent in the 15 IPAVA-positive raccoon dogs after supplementation with 100% oxygen ( BS0, 11; BS2, 4). Moreover, BS of the IPAVA showed a significant correlation with the cardiac output per body weight (BW). Conclusion: The prevalence of IPAVA in healthy raccoon dogs at rest was 75%. Adequate oxygen supplementation was found to be effective in reducing QIPAVA, which may help prevent potential negative factors such as pulmonary gas exchange impairments and paradoxical embolism that can occur with IPAVA.